THERAPY CENTER FOR CHILDREN LEARNING DISORDERS WITH BIOPHILIC DESIGN APPROACH - Kania H G W, Shelvie
In Indonesia 10% - 15% of school children suffer from learning disorders. With the number of school children in Indonesia around 50 million, it is estimated that 5 million of them have learning disorders. Learning disorders that are commonly found in children include dyslexia, dysgraphia, dyscalculia, dyspraxia, non-verbal learning disabilities and auditory processing disorder. Children who have learning disorders will usually experience obstacles in their learning activities such as concentration, memory disorders, reading disorders, writing disorders, counting and others. Formal education is not enough for children with learning disorders, with a low level of academic understanding, children with learning disorders need to be trained continuously to be independent on learning so that they can balance normal children by doing a learning therapy. Unfortunately, in Indonesia there is no special therapy center for children with learning disorders with good space facilities, in terms of the effectiveness of the learning therapy process physically, emotionally, and mentally. Therapy Center for Children Learning Disorders is a therapy facility design that accommodates learning therapy activities for children with learning disorders using a biophilic design approach to interior space elements which are believed could provide good benefits such as increasing physical comfort, increasing cognitive abilities, concentration and memory levels for children with learning disorders. The design method was conducted through qualitative data collection. The data collection was carried out through literature study, observation, survey, and interview. The concept of 'Growing by Nature' was chosen because it describes the hope for children with learning disorders to develop into better individuals in the academic and non-academic fields through a natural approach. This concept is reduced to three keywords Growth, Zestful, and Dynamic which are implemented in the use of shapes, colors, materials, and furniture that represent and are in accordance with the needs of children with learning disorders.